Nonglucuronidated Ezetimibe Disrupts CD13‐ and CD64‐Coassembly in Membrane Microdomains and Decreases Cellular Cholesterol Content in Human Monocytes/Macrophages. Issue 8 (17th April 2019) - Orsó, Evelyn; Robenek, Horst; Boettcher, Alfred; Wolf, Zsuzsanna; Liebisch, Gerhard; Kramer, Werner; Schmitz, Gerd
Abstract: Ezetimibe (EZE) and glucuronidated EZE (EZE‐Glu) differentially target Niemann‐Pick C1‐like 1 (NPC1L1) and CD13 (aminopeptidase‐N) to inhibit intestinal cholesterol absorption and cholesterol processing in other cells, although the precise molecular mechanisms are not fully elucidated. Cellular effects of EZE, EZE‐Glu, and the low‐absorbable EZE‐analogue S6130 were investigated on human monocyte‐derived macrophages upon loading with atherogenic lipoproteins. EZE and S6130, but not EZE‐Glu disturbed the colocalization of CD13 and its coreceptor CD64 (Fcγ receptor I) in membrane microdomains, and decreased the presence of both receptors in detergent‐resistant membrane fractions. Biotinylated cholesterol absorption inhibitor C‐5 (i.e., derivative of EZE) was rapidly internalized to perinuclear tubular structures of cells, resembling endoplasmic reticulum (ER), but CD13 was detected on extracellular sites of the plasma membrane and endolysosomal vesicles. Administration of EZE, but not of EZE‐Glu or S6130, was associated with decreased cellular cholesteryl ester content, indicating the sterol‐O acyltransferase 1 (SOAT1)‐inhibition by EZE. Furthermore, EZE decreased the expression of molecules involved in cholesterol uptake and synthesis, in parallel with increased apolipoprotein A–I‐mediated cholesterol efflux and upregulation of efflux‐effectors. However, NPC1L1 the other claimed molecular target of EZE, was not detected in macrophages, thereby excluding this protein as target for EZE in macrophages. Thus, EZE is very likely a CD13‐linked microdomain‐disruptor and SOAT1‐inhibitor in macrophages leading to in vitro anti‐atherosclerotic effects through a decrease of net cellular cholesterol content. © 2019 International Society for Advancement of Cytometry Abstract :